Impact of proactive behavior on sustainable performance - et. al., Firas Mahdi Ali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to verify the impact of proactive behavior, an independent variable, on the sustainable performance of an approved variable, at the headquarters, divisions, and units of the General Automobile and Machinery Trading Company, to diagnose the level of interest of its leaders and subordinates in the research variables and their dimensions, as well as make recommendations that contribute to strengthening the practices of the three variables in the company in question. Given the fact that the researcher is keen to diagnose the impact relation between variables, because of their importance at the company's headquarters and its members, and because they reflect on the community, the researcher has adopted an exploratory approach to conduct the current research chapters. The research community has included the headquarters of the General Company for the Trade of Cars and Machinery, which includes 523 employees. The researcher targeted a class sample of 223 members, consisting of (General Manager, Associate General Manager, Section Manager, Associate Section Manager, Division Manager, garage manager, Unit Officer, Employee), adopting the questionnaire which is containing (40 paragraph), interviews, and field monitoring to enhance the practical aspect. The researcher used statistical programs (26. V. SPSS, 25. V. Amos) to analyze primary data, adopting descriptive and indicative statistical methods (natural distribution test, syntactic and exploratory factor analysis, percentage, arithmetic mean, standard deviation, relative difference coefficient, relative importance, Pearson correlation coefficient, simple linear regression coefficient, multiple regression coefficients) to test its hypotheses. The most notable findings of the research were that the proactive behavior has an impact on sustainable performance directly and indirectly, particularly through a broader role, self-competence and a sense of responsibility towards constructive change.